The Islamic Communication: One Persuasive Step to Spread Da’wah Among Korean Lovers (Critical Discourse Analysis of Fuadh Naim's Youtube) - Wijaya, Adi Wijaya (TASAMUH, 2024)
Making people closer to Islam is one of da'wah's primary goals. So, it takes creativity to package da'wah messages so that they can be accepted by the object of da'wah, which is increasingly diverse today. One of the interesting da'wah objects studied is Korean Lovers, a community of Korean culture lovers. A negative stigma has been pinned on Korean Lovers, that they are a community far from Islam and live with hedonistic nuances. Meanwhile, with the right da'wah approach, Korean Lovers can be touched and become part of Islamic da'wah. This study aims to analyze how da'wah content includes or removes actors from a central discourse. Furthermore, the analysis results are linked to the concept of Islamic communication. This is where the novelty lies. This research makes the Never Drowned video on Fuadh Naim's YouTube channel the main discourse (object of research). Fuadh Naim's YouTube channel discusses Korean culture and gets positive appreciation. The PernahTenggelam video can reference the style of delivering da'wah messages among Korean Lovers. To elaborate on the #PernahTenggelam video, the most appropriate method used is qualitative analysis with Theo van Leuween's critical discourse analysis model. The results showed that 18 data were analyzed. Of the 18 data, 3 showed an exclusion strategy, and 15 showed an inclusion strategy. After being analyzed, the results show that content creators do not intend to discredit Korean Lovers. Instead, the exclusion and inclusion made the delivery more elegant and persuasive. The strategy is connected with Islamic communication, including qaulan sadida, qaulan ma'rufa, qaulan baligha, qaulan maysura, and qaulan layyina.